A COMPREHENSIVE EXPLORATION OF MOBILE APPLICATION TYPES IN EDUCATION AND THEIR CONTRIBUTION TO EFFECTIVE LEARNING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The rapid advancement of mobile technologies has reshaped educational systems worldwide by providing new opportunities for flexible, personalized, and interactive learning. Mobile applications now function as essential digital tools that support instruction, assessment, collaboration, content mastery, and skill development across diverse disciplines. This article presents an extended academic overview of categories of educational mobile apps, exploring their pedagogical functions, cognitive value, and implications for modern digital learning environments. Supported by scholarly literature, the analysis emphasizes how mobile apps enhance learner autonomy, foster motivation, and contribute to the development of 21st-century competencies.